(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa: la pronuncia della Corte costituzionale e i nodi da sciogliere - 2. I limiti legittimi alla libertà religiosa - 3. Gli interventi positivi a favore del diritto al culto - 4. Brevi considerazioni conclusive: che cosa farà (o, meglio, cosa dovrebbe fare) il legislatore regionale? The Constitutional Court’s position about worship facilities between limits against the freedom of religion and positive interventions ABSTRACT: The Constitutional Court has another time pronounced about the right to have a place of worship. Its statements are crucial for this subject and are likely to produce an echo even outside the field of worship facilities. In particular, the Court affirms, on the one hand, that the freedom of worship might be limited only in order to guarantee concrete opposing interests, and not for mere exigencies of control. On the other hand, the Court declares that the freedom of religion, given its central and essential position in the Constitution, legitimizes and requires positive interventions by the legislator, in order to be promoted.